Concussion incidence and recovery in Swedish elite soccer - prolonged recovery in female players - Vedung, F.; Hänni, S.; Tegner, Y.; Johansson, J.; Marklund, N. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Sport-related concussions are an increasingly recognized health problem. Soccer is the most popular sport in the world although recent studies on concussion incidence are scarce. Here, a nation-wide prospective study on concussion incidence, symptom severity, risk factors, gender differences and return-to-play after concussion was performed in 51 Swedish elite soccer teams during the 2017 season. Methods: In the first and second soccer leagues for men and women, a Sport Concussion Assessment Tool (SCAT) -based questionnaire study was performed at pre-season (baseline) and from 48h up to three months post-concussion. Results: We followed 959 players (389 women, 570 men) for 25146 player game hours (9867 h for women, 15279 h for men). Concussion incidence (n= 36) was 1.19/1000 player game hours (females 1.22/1000 h, males 1.18/1000 h; p= 0.85). Twenty-seven percent (females 8%, males 40%) of players continued to play immediately after the concussion. When compared to male players, female players had worse initial symptom severity scores (median and IQR 30 (17-50.5) vs. 11 (4-26.25), p=0.02) and longer return to play (p=0.02). Risk factors for concussion were baseline symptoms and previous concussion. Conclusion: In Swedish elite soccer, the concussion incidence was 1.19/1000 without gender differences. Most players recovered to play within four weeks post-injury. Almost one third of players continued to play at time of concussion. Female players had worse initial symptoms and longer return-to-play time than males, and a prolonged recovery beyond three months was only observed among female players.